Glutamine and the immune system - Cruzat, Vinicius; Newsholme, P. (2017)
© 2018 by Taylor & Francis Group, LLC. Glutamine is recognized as a crucial and versatile amino acid for cell survival and growth, playing an important role in metabolism. Moreover, compared to all other amino acids in the body, glutamine is present at the highest extracellular concentration, and is considered the most abundant free amino acid. In fact, in addition to glucose, glutamine represents a primary nutrient for maintenance of the body’s homeostasis (Newsholme et al. 2003a).